Percurso de desenvolvimento de árbitros brasileiros do atletismo - Campos, Thamires Silva (2023)
Sport is one of the greatest sociocultural phenomena of the 21st century. It is a heritage of humanity that originated from the symbologies and human relationships throughout history. In this universe, the referee is an actor of fundamental importance, whose function is to mediate the game environment and ensure the application of rules for each modality. In a bioecological perspective of human development, it is considered that the responsible before being an actor in the show, is a person who, being part of society as a whole, influences and is influenced by the environment in which he is involved. In this way, the investigation of the processes along the path of development of addiction, makes it possible to understand the factors that drive and motivate the subject in the arbitration career. This project aims to analyze, from the bioecological perspective of human development, the factors that determine the formation of immune systems. This is a retrospective-descriptive research with a qualitative approach, guided by the PPCT model (Process, Person, Context and Time) developed by Urie Bronfenbrenner. An interview guided by a semi-structured judgment was carried out, in addition to the documentary analysis of the development path of the pilots. There were 9 passives, affiliated to the Brazilian Athletics Confederation (CBAt), active in national and international competitions, of both sexes, who had Level II and III titles. It is expected that the testimonies of the participants can provide information about the development path and present perspectives for future self-employed workers in the category. It is also envisaged to reflect on the existing interventions in the daily life of arbitration that are supporting to captivate people for the career of arbitration in this modality.